Abnormal focal segments in left uncinate fasciculus in adults with obsessive–compulsive disorder - Zhang, Suming; Li, Bin; Jiang, Jiaxin; Hu, Xinyu; Li, Hailong; Cao, Lingxiao; Zhou, Zilin; Liang, Kaili; Zhou, Huan; Zhang, Lianqing; Gong, Qiyong; Huang, Xiaoqi (Frontiers in Psychiatry, 2023)
Background: Although the specific role of the uncinate fasciculus (UF) in emotional processing in patients with obsessive-compulsive disorder (OCD) has been investigated, the exact focal abnormalities in UF have not been identified. The aim of the current study was to identify focal abnormalities in the white matter (WM) microstructure of the UF and to determine the associations between clinical features and structural neural substrates. Methods: In total, 71 drug-naïve patients with OCD and 81 age- and sex-matched healthy controls (HC) were included. Automated fiber quantification (AFQ), a tract-based quantitative approach, was adopted to measure alterations in diffusion parameters, including fractional anisotropy (FA), mean diffusivity (MD), radial diffusivity (RD) and axial diffusivity (AD), along the trajectory of the UF. Additionally, we utilized partial correlation analyses to explore the relationship between the altered diffusion parameters and clinical characteristics. Results: OCD patients showed significantly higher FA and lower RD at the level of temporal and insular portion in the left UF than HC. In the insular segments of the left UF, increased FA was positively correlated with the Hamilton Anxiety Scale (HAMA) score, while decreased RD was negatively correlated with the duration of illness. Conclusion: We observed specific focal abnormalities in the left UF in adult patients with OCD. Correlations with measures of anxiety and duration of illness underscore the functional importance of insular portion of left UF disturbance in OCD.